Implementing extended producer responsibility for tyre waste in Togo: a circular economy perspective - Narra, Mona-Maria; Agboka, Komi; Narra, Satyanarayana; Nelles, Michael (Frontiers in Sustainability, 2025)
End-of-life tyre (ELT) management presents significant challenges in West Africa, particularly in Togo where an estimated 30,500 tonnes accumulate annually from imported used tyres and second-hand vehicles. Current disposal practices create substantial environmental and public health risks, with 65% of tyres burned and 25% dumped. Comprehensive field investigations examined the origin and manufacturer profiles of ELTs in Togo, while various Extended Producer Responsibility (EPR) models were assessed for local applicability. A novel three-pronged approach was developed combining import levies on tyres, manufacturer-centric responsibility mechanisms, and government financial incentives. This integrated framework addresses the imbalance where multinational tyre manufacturers benefit economically while contributing minimally to waste management costs. Analysis indicates that successful implementation requires adaptation to local economic, social, and infrastructural realities. The proposed EPR model targets environmental degradation mitigation while creating sustainable economic opportunities within the region. The framework offers potential application as a template for similar initiatives across West Africa.